Efektivitas Direct Method (Thoriqoh Mubayaroh) dalam Pembelajaran Bahasa Arab di Madrasah Alsun Sidoarjo - Anggar wicaksono; Hisbullah Huda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to find out the direct method in Arabic language education at Madrasah Alsun Sidoarjo, as well as to identify the inhibiting and supporting factors. With this research it is hoped that it can provide new input to all parties involved in Arabic language education in general and especially at Alsun Sidoarjo Madrasah. This research is a mixed research between qualitative and quantitative. Qualitative research is primary research and quantitative research is complementary research to find data using numbers. Information collection was attempted by observation, documentation, interviews, questionnaires by organizing facts or observations and quantitative data so that conclusions were drawn from these results. The results of this study show that direct procedures in Arabic language education at Madrasa Alsun Sidoarjo have been good. this can be proven by the results of a questionnaire that the author has done, namely 80% of students can master the lessons given. Second, the learning effectiveness of students in Arabic language education through direct procedures has been efficient. This matter can be proven by the test results which after being calculated by the statistical formula Mx=Fx:N, the result is 85.5.